Quantification of Total Polyphenols, Total Flavonoids, and Evaluation of Antioxidant Activity of the Aerial Part of Distichochlamys orlowii K. Larsen & M.F. Newman - Tung, Nguyem Xuan; Hai, Nguyen Thanh; Hong, Le Thi; Anh, Nguyen Thi Van; Luyen, Le Hong (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Distichochlamys orlowii K. Larsen & M.F. Newman is a type of ginger endemic to Vietnam with high values of usage. This study aims to evaluate the total phenolic content, total flavonoid content, and antioxidant effect of the aerial part of Distichochlamys orlowii . The medicinal samples were extracted by ultrasonic method with different solvents including methanol, ethanol, ethyl acetate, and dichloromethane. The total phenolic content was evaluated using the Folin-Ciocalteu reagent and the total flavonoid content was evaluated by the aluminum chloride colorimetric method. The in vitro antioxidant effects of extracts were investigated through free radical scavenging models with DPPH and ABTS. The obtained results showed that the ethanol extract contained the highest content of total phenolic content and total flavonoid content with values of 12.81 ± 0.05% and 19.52 ± 0.23%, respectively. Meanwhile, the methanol extract exhibited the strongest DPPH and ABTS free radical scavenging activities with IC 50 values of 243.89 ± 5.98 µg/mL and 33.58 ± 3.14 µg/mL, accordingly. The IC 50 values of positive controls were 7,88 ± 0,25 µg/mL for the former assay and 9,74 ± 0,36 µg/mL for the latter assay. This is the first report on the chemical composition and antioxidant activity of the extracts from the aerial part of Distichochlamys orlowii .